EMPIRICAL ANALYSIS OF THE ALGORITHM FOR FINDING ALL MINIMUM-HOP PATHS IN NETWORKS - Džonova-Popova, Iskra K. (Matematichki Bilten, 1995)
A fairly simple, but quite useful extension of Dijkstra’s shortest path algorithm for finding all minimum-hop paths in networks was presented in [1]. In order to pursue empirical study of the previous analytical results, both the rudimentary and the modified algorithm were implemented upon a simple of randomly generated networks. The results obtained confirm the relationship concerning the computational complexity of both algorithms, namely that they are of same order in their requirement of the computing resources.